Análise teórica e experimental de vigas de alvenaria estrutural sujeitas ao cisalhamento - Pasquantonio, Rafael Dantas (Universidade Federal de São Carlos, 2015)
This study intends to analyze, in the construction system that is in ascendancy - the structural masonry, an element that demands a special attention comparing to other elements: the reinforced concrete masonry beam. The beams carry vertical loads, with flexure and shear forces. In the theoretical part, the literature review included national and international papers and codes. The assessed codes were the national (NBR15961-1/2011 and NBR 6118/2014) and international (ACI530-13, AS3700/2001, S304/2014 and Eurocode 6.1/2001). The experimental study includes testing of ten (10) concrete block masonry beams, designed to fail due to shear forces. As a conclusion, it can be pointed that concrete masonry beams failure in a similar behavior to concrete beams, except for some particularities such as prior joint cracking. Furthermore, the specification at Brazilian and European standards led to considerably higher results than the experimental results while the specifications at ACI530-13, AS3700/2001, S304/2014 and NBR6118/2014 yielded reasonable predicted values when compared to experimental results.
Keywords: Viga; Alvenaria; Alvenaria armada e cisalhamento; Beam; Masonry; Reinforced masonry and shear; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL